ANALISIS PEMASARAN KUBIS (Brassica oleracea L.) (Studi Kasus Di Kelompok Tani Bumi Jaya 01 Desa Kaponan Kecamatan Pakis Kabupaten Magelang) - Adrika Melya Husna; Renan Subantoro; Istanto Istanto (Universitas Wahid Hasyim, 2020)
Cabbage is one of the agricultural commodities that is perishable, so it must be immediately distributed to consumers through the marketing process. The length of a marketing channel can affect marketing margins, farmer's share, profit to cost ratio, and marketing efficiency. The aims of this study is to determine the marketing channels, marketing margins, farmer's share, and profit to cost ratio, and the efficiency of marketing channels. The research method used is descriptive method and the determination of the location of research carried out purposively. Determination of farmer respondents using the census method and determination of trader respondents to consumers using the snowball sampling method. Based on the results of the study there are four cabbage marketing channels in the Bumi Jaya 01 Farmers Group Kaponan Village, Pakis District, Magelang Regency, namely zero level channels (farmers-consumers), first level channels (farmers- retailers-consumers), second level channels (farmers-collectors-retailers-consumers), and third-level channels (farmers-collectors-wholesalers-retailers- consumers). Marketing margins, farmer's share, and profit to cost ratio for each channel, for level 0 channels are Rp. 0/kg, 100%, and Rp. 4,16/kg, level 1 channels are Rp. 400/kg, 77,14%, and Rp. 5,29/kg, level 2 channels are Rp. 1.225/kg, 36,25%, and Rp. 2,26/kg, level 3 channels are Rp. 2.825/kg, 19,29% and Rp. 5,21/kg. In the zero level and first level marketing channels the efficiency of marketing is efficient based on the calculation of marketing margins, farmer's share, and profit to cost ratio. Keywords: marketing channels, margins, farmer’s share, efficiency, cabbage